RESISTENSI SEKOLAH EKS-UNGGULAN TERHADAP KEBIJAKAN SISTEM ZONASI DALAM PENERIMAAN PESERTA DIDIK BARU (PPDB) DI KABUPATEN LUWU, SULAWESI SELATAN - Tawakkal Tawakkal; Saiful Saiful (Jurnal Administrasi Terapan, 2023)
The implementation of zoning system policies in the ex-superior Senior High School Luwu Regency, South Sulawesi. In its implementation, it was found that the implementers had their own strategies in responding to the PPDB zoning system policy, resulting in an uneven distribution of students in each school.The attitude of the implementers is reinforced by the theory of policy resistance. In addition, there are also several obstacles in its implementation, such as zoning which is more profitable for ex-superior schools, lack of socialization by related agencies, insufficient school facilities in all schools, especially non-superior ones, and the use of family cards and wishes parents so that their children get a better education. This study used a qualitative descriptive method with data collection techniques through interviews and direct observation at the research location and was supported by secondary data and documents in each school and from the Education Office. The main resource person in this research is the principal, but to support the research data that has been obtained, researchers also collect data from other sources, such as; teachers and education personnel (curriculum, student affairs, school treasurers, and school operators) and also supported by non-bureaucratic parties (journalists, political parties, NGOs (non-governmental organizations), and youth activists in the education sector. In order to achieve the main objectives of the zoning system policy, researchers recommend that local governments force more implementors in each ex-superior school to comply with the policy and impose sanctions in accordance with the applicable Permendikbud.